Factors of activity of the troops of NKVD of the USSR during the East Prussian strategic offensive operation - A. S. Chentsov (Омский научный вестник: Серия "Общество. История. Современность")
The article discusses the factors influencing the activities of the troops of NKVD of the USSR, providing protection for the rear of the army in the period of the East Prussian strategic offensive operation. Sources are introduced into scientific circulation, which made it possible to identify two groups of factors that influenced the activities of the troops of NKVD of the USSR. The first is external. These include the peculiarities of the situation on the territory of East Prussia. The second is internal. They include changes in the command and control system and the structure of the troops, as well as new tasks, the implementation of which was entrusted to the troops of NKVD of the USSR. The author comes to the conclusion that taking into account these factors is the basis for identifying the features of the operational activities of the troops of NKVD of the USSR during the East Prussian strategic offensive operation.